2022
DOI: 10.1371/journal.pone.0266700
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution and environmental risks in the water of Rongna River caused by natural AMD around Tiegelongnan copper deposit, Northern Tibet, China

Abstract: Acid mine drainage (AMD) is one of the biggest environmental challenges associated with in the mining process. Most of the current research on AMD focuses on developed deposits, whereas there is almost no research on naturally-produced AMD from undeveloped deposits. In this study, river water and AMD were collected to analyze the distribution characteristics of heavy metals and the phytoplankton community. In addition, the environmental risks of heavy metals were evaluated by single-factor pollution index, Nem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…4E). Moreover, the operational range was within the range of Cu 2+ concentrations found in polluted environments 5759 , validating the potential use of this sensor as a relevant Cu 2+ monitoring tool. These results confirmed that structure-guided mutagenesis indeed can be used to restore protein functionality following construction of MerR hybrid proteins.…”
Section: Resultssupporting
confidence: 61%
“…4E). Moreover, the operational range was within the range of Cu 2+ concentrations found in polluted environments 5759 , validating the potential use of this sensor as a relevant Cu 2+ monitoring tool. These results confirmed that structure-guided mutagenesis indeed can be used to restore protein functionality following construction of MerR hybrid proteins.…”
Section: Resultssupporting
confidence: 61%
“…MerRCueR mut3 provided the highest RLU/OD 600 output at each concentration and an LOD (10 μM) below the EPA guideline value of 20.45 μM (Figure E). Moreover, the operational range was within the range of Cu 2+ concentrations found in polluted environments, validating the potential use of this sensor as a relevant Cu 2+ monitoring tool. These results confirmed that structure-guided mutagenesis indeed can be used to restore protein functionality following construction of MerR hybrid proteins.…”
Section: Results and Discussionmentioning
confidence: 99%
“…According to Bhuyan et al, 2019 study, for Old Brahmaputra river, Bangladesh, concentration of Pb ranged between 4.8 to 9.8 mg/kg in sediment, with the highest concentration (9.8 mg/kg) at Belanagor in post-monsoon and water Pb concentration were between 0.01 to 0.21 mg/l. After entry of natural acid mine drainage to Rongna river, heavy metal concentrations were significantly greater compared to Bolong river, control samples, with Pb concentrations were reported at 3 times for the former with relation to the latter, statistical analysis indicated the presence of Pb may have been due to rock weathering (Luo et al, 2022). Astatkie et al, 2021 study for Awatu watershed, Ethiopia indicated high concentration of sedimentary Pb, with mean value 2005.94 mg/kg, correlation analysis showed that heavy metals had common anthropogenic pollution sources due to rapid urbanization and discharging of water inappropriately.…”
Section: Introductionmentioning
confidence: 88%